Pengolahan Kotoran Sapi dan Limbah Tandan Kosong Kelapa Sawit Menjadi Pupuk Organik di Desa Mambang Kecamatan Muara Kelingi Kabupaten Musi Rawas - Linna fitriani Linna; Reny Dwi Riastuti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The majority of the people in Mambang Village make a living as oil palm farmers and cattle breeders. Fertilizer prices are relatively expensive and also scarce causing economic difficulties. Cow dung produced from animal husbandry and empty fruit bunches of oil palm is not utilized optimally so it only creates waste. The right solution is needed to overcome this problem by processing cow dung and palm oil empty sign waste as organic fertilizer that can be utilized by the community and generate economic benefits. Implementation method with socialization, training, and processing of organic fertilizer. Based on the stages of implementation, there was an increase in community knowledge and skills in processing organic fertilizer from cow dung and oil palm empty sign waste. Produced organic fertilizer products that can be used by the surrounding community. Based on this community service activity, the community can process it into organic fertilizer. In this service activity, it is necessary to test the content of the results and research on organic fertilizers.